Nanoemulsified Butenafine for Enhanced Performance against Experimental Cutaneous Leishmaniasis - Bezerra-Souza, Adriana; Jesus, Jéssica A.; Laurenti, Márcia D.; Lalatsa, Aikaterini; Serrano, Dolores R.; Passero, Luiz Felipe D. [UNESP] (Hindawi, 2021)
The production of ergosterol lipid involves the activity of different enzymes and is a crucial event for the Leishmania membrane homeostasis. Such enzymes can be blocked by azoles and allylamines drugs, such as the antifungal butenafine chloride. This drug was active on parasites that cause cutaneous and visceral leishmaniasis. Based on the leishmanicidal activity of butenafine chloride and considering the absence of reports about the therapeutic potential of this drug in cutaneous leishmaniasis, the present work is aimed at analyzing the efficacy of butenafine formulated in two different topical delivery systems, the self-nanoemulsifying drug delivery systems (BUT-SNEDDS) and in a SNEDDS-based nanogel (BUT-SNEDDS gel) as well as in the free form in experimental cutaneous leishmaniasis. Physical studies showed that both formulations were below 300 nm with low polydispersity (<0.5) and good colloidal stability (around -25 mV). Increased steady-state flux was reported for nanoenabled butenafine formulations with reduced lag time in Franz cell diffusion assays across Strat-M membranes. No toxic or inflammatory reactions were detected in animals treated with BUT-SNEDDS, BUT-SNEDDS gel, or butenafine. Animals topically treated with butenafine (free or nanoformulated) showed small dermal lesions and low tissue parasitism. Furthermore, BUT-SNEDD gel and butenafine presented similar efficacy than the standard drug Glucantime given by the intralesional route. Increased levels of IFN-γ were observed in animals treated with BUT-SNEDDS gel or butenafine. Based on these data, the antifungal drug butenafine chloride can be considered an interesting repurposed drug for the treatment of cutaneous leishmaniasis.